Property rights, collective action and technologies for natural resource management: a conceptual framework - Knox, Anna; Meinzen-Dick, Ruth S.; Hazell, Peter B. R. (International Food Policy Research Institute, 1998)
This paper explores how institutions of property rights and collective action play a particularly important role in the application of technologies for agriculture and natural resource management. Those technologies with long time frames tend to require tenure security to provide sufficient incentives to adopt, while those that operate on a large spatial scale will require collective action to coordinate, either across individual private property or in common property regimes. In contrast to many crop technologies like highyielding variety seeds or fertilizers, natural resource management technologies like agroforestry, watershed management, irrigation, or fisheries tend to embody greater and more varying temporal and spatial dimensions. Whereas the literature addressing constraints and enabling factors for rural technology adoption have largely focused on their direct effects on crop technologies, the conceptual framework presented here shows how property rights and collective action interact with many other constraints to technology development (such as wealth, information, risk, or labor availability). The paper further explores how the structure of property rights and collective action shape the efficiency, equity and environmental sustainability of technological outcomes, thereby enriching our understanding of different technologies’ contributions to poverty alleviation.